Lck and the nature of the T cell receptor trigger. - Davis, S; Van Der Merwe, P (2011)
Exactly how ligand binding 'triggers' T cell receptor (TCR) phosphorylation is unclear. It has been proposed that ligand engagement by the TCR somehow activates the Src kinase Lck, which in turn phosphorylates the receptor. Recent data, however, suggest instead that a significant fraction of the Lck in resting T cells is already activated and that the proportion of active Lck does not change during the early stages of T cell activation. We argue that, caveats notwithstanding, these new observations offer support for the 'kinetic-segregation' model of TCR triggering, which involves spatial reorganization of signalling proteins upon ligand binding and requires a fraction of Lck to be active in resting T cells.